Penerapan Teknologi Robot Hydraulic dan Line Follower (HLF) untuk Pemberian Pakan di Industri Peternakan Sapi - Yoga Supra Yoga; Angel Puspita Wulandari; Nining Suningsih (Seminar Nasional Lahan Suboptimal, 2019)
Yoga YS, Wulandari AP, Suningsih N.  2019. Application of hydraulic and line follower (HLF) robot technology for feeding in the cattle industry. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 513-521 . Palembang: Unsri Press. The livestock system in Indonesia still uses conventional and minimal technology farming systems, one of which is in the field of feeding, especially medium-scale cattle and industry which consumes a lot of energy when feeding manually. Innovations offered to farmers include robotics technology. The technology in question is a hydraulic and Line Follower (HLF) robot. Hydraulics robot is a type of robot that uses liquid pressure as its driving force while the Robot Line Follower is a feed distribution robot that utilizes sensor technology. Robot Line Follower can move on its own by using a sensor line that will be made to follow the direction of the animal feed so that the robot can distribute feed to existing livestock. The purpose of writing this scientific paper is for medium-scale farmers and industry to know how to assemble Hydraulic and Line Follower robots, HLF robot work, process of using robots and know the advantages of applying HLF robot technology. The scope of this scientific article is in the fields of technological innovation, animal husbandry, and the food industry. The problems that will be examined in this scientific article consist of: how to assemble HLF robots, how to work HLF robots, HLF robot applications in cattle farms and the advantages of HLF Robot application. The idea of this article is sourced from surveys to cattle farms to obtain data and analysis of the work mechanism of animal feed and literature studies to strengthen opinions. The conclusion of this scientific article is the existence of robotics technology in the field of animal husbandry will further assist farmers in carrying out existing work so that it can be more efficient and profitable for farmers.Keywords: hydraulic robot, line follower robot, livestock industry, robotic technology